Faktor Pemanfaatan Imunisasi Inactivated Polio Vaccine (IPV) - Icon Harizon; Misnaniarti Misnaniarti; Haerawati Idris (Politeknik Kesehatan Tanjung Karang, 2020)
The low utilization of IPV immunization services in Palembang in 2017 was 66,7% while the national target was 95%. The purpose of this study was to determine the factors associated with the utilization of IPV immunization services in Palembang. The study was conducted in September-October 2018, the population was 3570 mothers who had babies who were targeted by IPV immunization, 400 samples of mothers who have babies are targeted by IPV immunization in 5 health centers in Palembang by random sampling. Research using quantitative methods with cross-sectional design. Data collection instruments were questionnaires based on the concept of health trust models, interviews, and observations, the data were analyzed using multiple logistic regression. The results showed that 84.5% of mothers used IPV immunization services in Palembang. The results of multiple logistic regression showed that the family support variable (PR=2,015), knowledge of the mother variable (PR=2,164), the availability of health care facility variables (PR=2,376), and variable support for health workers (PR=3,601) affect the utilization of IPV immunization services in Palembang City. Conclusion: variable support for health workers is the variable that has the greatest influence on the utilization of IPV immunization services in Palembang.